PENGEMBANGAN BUKU EKSPLORASI SAINS BERTEMA BERPETUALANG KE PALUNG MARIANA UNTUK MENUMBUHKAN KEMAMPUAN PROBLEM SOLVING ANAK USIA DINI - Ilzam Dhaifi; Taufiqurrahman; Minhaji (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2025)
Problem-solving ability is an essential aspect of early childhood cognitive development, as it shapes logical, critical, and creative thinking from an early age. However, many early childhood learning practices still focus on rote activities that do not sufficiently stimulate higher-order thinking skills. This study aims to analyze the effect of digital learning media on improving problem-solving abilities among early childhood students. The research employed a quasi-experimental design with a one-group pretest-posttest model involving 32 children in group B at an early childhood education institution in Situbondo. Data were collected through observation sheets assessing children’s problem-solving abilities and analyzed using simple linear regression. The results indicate a positive and significant influence between the use of digital media and children’s problem-solving ability (r = 0.61; p < 0.05) with the regression equation Y = 14.86 + 0.40X. The coefficient of determination (R²) value of 0.37 shows that 37% of the variation in problem-solving ability is explained by the use of digital media. These findings confirm that digital media is effective as an interactive and engaging learning tool that enhances critical thinking and problem-solving skills in early childhood education.